Contactors and relays susceptibility to voltage sags - Mohd Yazid Zaimuri (Universiti Malaysia Perlis, 2009)
A contactor is electrically controlled switch used for switching a power circuit and activated by a control input which is a lower voltage or current than that which the contactor is switching. While a relay is an electrical switch that opens and closes under the control of another electrical circuit. In the original form, the switch is operated by an electromagnet to open or close one or many sets of contacts. Voltage sags are brief reductions in voltage from 0.1 to 0.9 p.u. in rms voltage at the power frequency for durations from 0.5 cycles (8ms) to 1 minute. Sags are the most common power disturbance. At a typical industrial site, it is not unusual to see several sags per year at the service entrance, and far more at equipment terminals. These two components are problematic network components from sag point of view. Both of these component control motors which keep complex industrial processes running. For an example, unintended tripping of one motor feeder may bring the whole process down or even worse, bring it to a state which difficult to restore back to a normal condition. In this project a Programmable software, Schaffner Profline 2100 EMC is used to generate the voltage sag. The equipment under test such as contactor and relay will be fed up with various depth and duration of sag. The characteristic of the equipment will be recorded. In other words, this research bring to the study of voltage sag tolerance level, the effects and causes to the two above equipments and all the characteristic when they operate in sags condition. Experiments done mostly result in various changes of characteristics to contactors and relays. Furthermore, the effects to the load such as blinking and flickering can be seen. The waveforms captured showed the effects clearly such as the spikes of the current and decrease in rms voltage.